2018
DOI: 10.1165/rcmb.2017-0308oc
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis-induced Lung Vascular Leakage Contributes to the Development of Pulmonary Hypertension

Abstract: Although hemolytic anemia-associated pulmonary hypertension (PH) and pulmonary arterial hypertension (PAH) are more common than the prevalence of idiopathic PAH alone, the role of hemolysis in the development of PAH is poorly characterized. We hypothesized that hemolysis independently contributes to PAH pathogenesis via endothelial barrier dysfunction with resulting perivascular edema and inflammation. Plasma samples from patients with and without PAH (both confirmed by right heart catheterization) were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…Besides heme, ferrylHb but not Hb or metHb induces upregulation of adhesion molecules in ECs, but interestingly, this response is not dependent on TLR4 activation (16). Increased endothelial permeability contributes to inflammatory cell extravasation upon hemolysis, and previous studies showed that ferrylHb and free heme induce the loss of endothelial integrity (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 92%
“…Besides heme, ferrylHb but not Hb or metHb induces upregulation of adhesion molecules in ECs, but interestingly, this response is not dependent on TLR4 activation (16). Increased endothelial permeability contributes to inflammatory cell extravasation upon hemolysis, and previous studies showed that ferrylHb and free heme induce the loss of endothelial integrity (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 92%
“…Fourteen days post-MCT/vehicle treatment; animals were anesthetized with Inactin (Sigma-Aldrich, T133) at the dosage of 100 mg/kg, i.p. A customized pressure transducer catheter (SPR-513, Millar Instruments, Houston, TX) was inserted through the right jugular vein and advanced into the right ventricle (RV) to monitor right ventricular systolic pressure (RVSP) and right ventricular diastolic pressure (RVDP) as described previously [17]. Briefly, the pressure transducer catheter was connected to a Millar Transducer Control Unit TC-510 and PL3504 PowerLab 4/35 data acquisition system (AD Instruments, Colorado Springs, CO) to continuously record RV pressure under small animal ventilator system (Harvard Rodent Ventilator-683; Harvard Apparatus, South Natick, MA).…”
Section: Hemodynamic Measurements and Sample Collectionmentioning
confidence: 99%
“…Recently, we have reported that patients with PH have increased levels of circulating free hemoglobin (Hb), a marker of hemolysis, which strongly correlated with the clinical characteristics of PH progression [17]. In the SU/Hx model, hemolysis was associated with an increased heme-mediated endothelial barrier dysfunction and formation of perivascular edema.…”
Section: Introductionmentioning
confidence: 99%
“…Akt nitration was induced by treatment with 3-morpholinosyndnomine (SIN-1) (1 mM) for 1 h. NP pretreatment groups were treated with 1 µM NP for 30 min, and then cells were washed in PBS and treated with SIN-1 for 1 h. All treatments were accompanied by including controls with the corresponding vehicle. After treatment, the cells were washed in PBS and lysed in RIPA buffer containing protease and phosphatase inhibitor cocktail [17].…”
Section: Sin-1 Induced Akt Nitration Assaymentioning
confidence: 99%